Peningkatan Kesiapsiagaan Gempa Bumi Anak melalui Media Edukatif Ular Tangga Siaga Gempa (UTSG) di Panti Asuhan Nurul Hasanah - Zelda Palin Ma’dika; Intan Febrina; Fitri Wulandari; Rizqisani Ramadhani; Fathin Aulia Rahman (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Indonesia is highly vulnerable to earthquakes due to its geological setting, making disaster preparedness an essential priority, particularly for children as one of the most vulnerable groups. This Community Service Program (CSP) aimed to improve the knowledge and earthquake preparedness of children at the Nurul Hasanah Orphanage through an interactive educational medium, the Earthquake Preparedness Snakes and Ladders Game (Ular Tangga Siaga Gempa/UTSG). The program employed a participatory learning approach combined with experiential learning. The activities consisted of a pretest, educational sessions, implementation of the UTSG game, an evacuation simulation, and a post test. The results demonstrated an improvement in participants’ knowledge of earthquake self-protection measures, evacuation procedures, and the identification of safe assembly points. In addition, participants were able to correctly perform evacuation procedures during the simulation, indicating enhanced practical skills in responding to emergency situations. The UTSG learning media also increased participants’ enthusiasm and active engagement by providing an interactive and enjoyable learning experience. In conclusion, game-based learning integrated with evacuation simulations is an effective approach to improving earthquake preparedness among children and has the potential to serve as an alternative disaster education medium for orphanages and other educational institutions.